Isu Gender dalam Perspektif Politik Islam - Sulthan Syahril (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
This article clarifies some gender bias issues which are importantly included into the Islamic political system. In addition, the Islamic political curriculum should take part in the effort to make people aware of the importance of gender equilibirium by establishing cultural perspective which is not discriminative against women. Gender sensitivity in Islam includes three main factors which require comprehensive methodological approach. They are: the fisrt, equilibrium issue related to the difference view of aurat (part of the body should be covered in Islamic law),the second, divorce and inheritance Islamic law, and the third, demand toward equal stance in politics. These three domains are supposedly important issues in Islamic political system.